A multicenter point prevalence survey of antibiotic use in Punjab, Pakistan: findings and implications. Issue 4 (3rd April 2019) - Saleem, Zikria; Hassali, Mohamed Azmi; Versporten, Ann; Godman, Brian; Hashmi, Furqan Khurshid; Goossens, Herman; Saleem, Fahad
ABSTRACT: Objectives : In line with the recent global action plan for antimicrobial resistance, this is the first time such a comprehensive antimicrobial point prevalence survey has been undertaken in Pakistan, the sixth most populous country. Methods : This point prevalence survey (PPS) was conducted in 13 hospitals among 7 different cities of Pakistan. The survey included all inpatients receiving an antibiotic on the day of PPS. A web-based application was used for data entry, validation, and reporting as designed by the University of Antwerp (www.global-pps.com). Results : Out of 1954 patients, 1516 (77.6%) were treated with antibiotics. The top three most reported indications for antibiotic use were prophylaxis for obstetrics or gynaecological indications (16.5%), gastrointestinal indications (12.6%) and lower respiratory tract infections (12.0%). The top three most commonly prescribed antibiotics were ceftriaxone (35.0%), metronidazole (16.0%) and ciprofloxacin (6.0%). Out of the total indications, 34.2% of antibiotics were prescribed for community-acquired infections (CAI), 5.9% for healthcare-associated infections (HAI), and 57.4% for either surgical or medical prophylaxis. Of the total use for surgical prophylaxis, 97.4% of antibiotics were given for more than one day. Conclusions : Unnecessary prophylactic antibiotic use is extremely high, and broad-spectrum prescribing is common among hospitals in Pakistan. There is an urgent need to work on the  national action plan of Pakistan on antibiotic resistance to address this.